Analysis of Mother's Knowledge of Giving MPASI to Infants Aged 6 -24 Months at Posyandu Flora Puskesmas Auxiliary Selemak Village - Suci Wulandari; Muniruddin Muniruddin; Latifah Latifah; Rahmasari Rahmasari (PROMOTOR, 2023)
Complementary Food for ASI (MP-ASI) is the provision of food other than breast milk, complementary food for ASI is given at least when the baby is 4 to 6 months old. The provision of complementary food for breastfeeding is said to be good if the food contains protein, nutrients, and energy, this is done so that the baby does not experience malnutrition or stunting. This study aims to determine the description of the mother with the characteristics of age, last education, and occupation on the provision of MP-ASI from an early age at the Flora Posyandu of the Selemak Village Community Health Center. The population in this study was 41 respondents using a total sampling technique. Data collection used a cross-sectional design using a questionnaire. This study concludes that the level of a mother's knowledge is very good based on age characteristics, last education, and mother's occupation so that she can provide MP-ASI to her baby at the right age, namely 6 -24 months.